Optimalisasi Modal Manusia, Struktural, dan Relasional dalam Meningkatkan Kinerja Keuangan: Studi pada Perusahaan Manufaktur Syariah - Titto Rafi’ Ramadhan; M. G. Kentris Indarti (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2025)
Financial performance is a crucial aspect in assessing the success of a company, both internally and externally. Capital structure, which reflects the proportion of debt and equity, plays a significant role in determining company performance. This study focuses on the sharia manufacturing sector in Indonesia, which contributes significantly to economic growth, with growth reaching 7.07% in the second quarter of 2021. The study analyzes the influence of intellectual capital, including human capital, structural capital, and relational capital, on financial company performance, with control variables such as company age and capital structure. Using Purposive sampling within 75 sharia manufacture companies on 3 years period 2021-2023. This study is limited to the sharia manufacturing sector and the 2021-2023 period, so generalization of the results should be done cautiously. These findings emphasize the importance of cost efficiency and resource allocation to improve financial performance, as well as the need for a deeper understanding of intellectual capital in formulating effective business strategies. The results show that capital structure has a positive also significant effect on Return on Assets (ROA), while company age has no significant effect on ROA. The regression model used is able to explain 23.5% of the variation in ROA, indicating the presence of other factors influencing company performance